Two-machine flowshop scheduling problem to minimize makespan or total completion time with random and bounded setup times - Ali Allahverdi; Tariq Aldowaisan; Yuri N. Sotskov (International Journal of Mathematics and Mathematical Sciences)
This paper addresses the two-machine flowshop scheduling problem with separate setup times to minimize makespan or total completion time (TCT). Setup times are relaxed to be random variables rather than deterministic as commonly used in the OR literature. Moreover, distribution-free setup times are used where only the lower and upper bounds are given. Global and local dominance relations are developed for the considered flowshops and an illustrative numerical example is given.